Nonlinear Blind Source Separation Algorithm Using Glowworm Swarm Optimization with Baffle Effect - Pubo Huang; Yu Wei (Dianxin kexue)
According to the characteristics of glowworm swarm optimization（GSO）algorithm, to overcome the disadvantages of premature convergence, a new method called “baffle effect”was proposed. The diversity of swarm was expanded. Based on the analysis of the model of nonlinear blind source separation（NBSS）, using traversing glowworm swarm twice, comparing evaluation function, the best result was get. Their validity is confirmed by effect of the signal separation test.